La paz de 1998 y su impacto en la relación Perú-Ecuador - Vidarte Arévalo, Oscar (2020)
Since 1998, the relationship between Peru and Ecuador has experienced a positive change. After decades of conflict, the bilateral approach has manifested itself through an intense cooperation dynamic in different areas, both political and economic. Thus, 20 years after the Peace Agreement, this article seeks to highlight the importance of solving the border problem for the achievement of these advances. So, emphasizing on the construction of interdependence and institutionality (concepts of the IR liberal tradition), we are going to demonstrate that the peace achieved laid the foundations for all the developments of the recent years, transforming the foreign policy of both countries. Unlike what it happened in the past, the perception that currently exists among Peruvians and Ecuadorians is different, and although there may always be problems between neighboring countries, the Peace Agreement has not only eliminated any potential war scenario, but it has also generated opportunities for joint development between Peru and Ecuador.